2014
DOI: 10.5465/amj.2011.0147
|View full text |Cite
|
Sign up to set email alerts
|

A Social–Structural Perspective on Employee–Organization Relationships and Team Creativity

Abstract: We develop a social-structural perspective on the relationship between employee-organization relationships (EORs) and team creativity. We argue that the mutual investment EOR approach, in which employers expect high levels of employee contributions and offer extensive inducements, will be associated with higher team creativity relative to other EOR approaches. We also advance the argument that this relationship will be mediated by team member work-related communication density and that the mediated relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 93 publications
1
111
0
5
Order By: Relevance
“…Tierney and Farmer (2002) [32] stated that high quality exchanges between team leader and employees could increase employee innovative behavior by influencing the employee's self-judgment. Other studies discovered that high quality exchanges within organizations also can bring positive outcomes (e.g., organizational commitment [17], individual performance [33], organizational citizenship behavior [34]). These studies provide evidence that high quality EOR will promote innovative behavior.…”
Section: Eor and Innovative Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Tierney and Farmer (2002) [32] stated that high quality exchanges between team leader and employees could increase employee innovative behavior by influencing the employee's self-judgment. Other studies discovered that high quality exchanges within organizations also can bring positive outcomes (e.g., organizational commitment [17], individual performance [33], organizational citizenship behavior [34]). These studies provide evidence that high quality EOR will promote innovative behavior.…”
Section: Eor and Innovative Behaviormentioning
confidence: 99%
“…The inducement-contribution model suggested that employers can motivate employees to make contributions to organization by providing them with inducements. Previous literature has found that EOR will promote employee positive psychology and behavior [15][16][17]. Hom et al (2009) [18] argued that employees' organizational trust might be a mediator mechanism between EOR and employee behaviors, different extents of EOR would lead to different individual outcomes via mediator (e.g., organizational trust).…”
Section: Introductionmentioning
confidence: 99%
“…It also had a comparative design exploring the perceptions of psychic distance by managers of both British and India SMEs who were engaged in partnerships. The paper was later published under the title 'Psychic Distance, Its Business Impact and Modes of Coping: A Study of British and Indian Partner SMEs' (Puthusserry, Child, & Rodrigues, 2014 (Jia et al, 2014). 3.…”
Section: Studies In the Chinese Context Are Also Crucial To The Identmentioning
confidence: 99%
“…We use the scale by Jia et al (2014) that entails signaled job expectations by the organization, building on employment relationship research (Wang et al, 2003). The scale comprises 13 items.…”
Section: Measures [Table 1 About Here]mentioning
confidence: 99%